Risk evaluation of type B aortic dissection based on WSS-based indicators distribution in different types of aortic arch. (June 2022) - Wen, Jun; Yan, Tingli; Su, Zhiqiao; Huang, Haodi; Gao, Qi; Chen, Xiaoyi; Wong, Kelvin K.L.; Peng, Liqing
Highlights: General level of time-averaged wall shear stress (TAWSS) was relatively low in type III aortic arch models. Traditional WSS-based indicators (TAWSS, OSI, RRT) show insignificant difference among different types aortic arch. Cross flow index (CFI) has a significant and positive relationship with type III aortic arch at segment of proximal descending aorta. The CFI, as a multidirectional WSS-based indicator, might be promising as a parameter for predicting the onset of type B aortic dissection (TBD). Abstract: Background and Objective: The underlying mechanism of aortic dissection (AD) remains unclear and the onset of AD is still unpredictable. Although clinical study with statistical analysis has reported that type III aortic arch may have strong correlation with type B AD (TBD), the effects of different arch types on the wall shear stress (WSS) have not been clarified. Methods: As a complementary work, this study numerically investigated the distribution of five WSS-based indicators in thirty aortic arches without AD, which were classified into three groups based on the arch types. Results: The distribution of most WSS indicators, such as time averaged WSS (TAWSS), oscillatory shear index (OSI) and relative residence time (RRT) had no significant difference among different types of aortic arches ( P >0.05). However, a multidirectional WSS index, namely CFI, was found its maximum value was positively correlated with type III aortic arch in proximal descending aorta ( p <0.001, r  = 0.65). Conclusions: It can be concluded that the enhancement or oscillation of WSS may not be the main reason of TBD is prevalence in type III arches, while the multidirectional WSS distribution may be an important factor. It can be further referred that the CFI may have a potential to predict the onset of TBD.